Depression in cancer patients - Vlad-Andrei David,; Rodica-Gabriela Enache, (Technium Social Sciences Journal, 2020)
As part of a more lengthy study major, this paper studies the prevalence of depression in cancer patients and the psychological impact that it has on them throughout the healing process. It is known as a fact that such a disease can cause damage not only to the patient's body, but also to his mind. Besides the symptoms of depression, a person that is suffering from cancer can develop other disorders. We researched certain studies that confirm this hypothesis, and as a consequence, we will try to come up with ideas to improve the methods of helping those in need of psychological aid.